Regional Patterns of Extreme Precipitation and Urban Signatures in Metropolitan Areas. Issue 2 (24th January 2019) - Zhang, Yongyong; Pang, Xuan; Xia, Jun; Shao, Quanxi; Yu, Entao; Zhao, Tongtiegang; She, Dunxian; Sun, Jianqi; Yu, Jingjie; Pan, Xinyao; Zhai, Xiaoyan
Abstract: Observations show that metropolitan areas throughout China, which are experiencing rapid urbanization, may have enhanced extreme precipitation. However, the underlying urban‐induced mechanism is poorly understood, particularly for entire characteristics of extreme precipitation. Focusing on the Beijing metropolitan area, we investigate regional patterns of extreme precipitation characterized by magnitude, frequency, duration, and timing metrics according to daily observations from 1975 to 2015 at 20 weather stations. Urbanization effects are explored by physical metrics of urbanization, including area, complexity, fragmentation, and dominance deduced from five periods of land use maps. Results show that the magnitudes and frequencies of extreme precipitation have decreased over time, the consecutive precipitation days have been extended, and the Julian date of maximum precipitation has been delayed. Temporal trends at 40% of weather stations are significant. According to precipitation metrics and geographical features, three representative regions are identified: the central urban region, the windward slope of topographic area, and the mountainous region. Compared with the metrics in mountainous region, the magnitudes of windward slope and central urban region are 24.3–60.6% and 5.9–47.3% greater, respectively; the frequencies are increased by 1.17 and 1.10 days, respectively; and the average date of maximum precipitation values are delayed by 7.0 and 4.0 days, respectively. The magnitudes and frequencies are enhanced by expansion of urban area, complexity, fragmentation, dominance, and heat islands. The durations are positive for urban area and dominance but negative for urban complexity, fragmentation, and heat islands. Furthermore, the effects in central urban region are more significant due to high urbanization rates. Key Points: Extreme precipitation metrics in central urban region and windward slope of topographic area are greater than those in mountainous region Magnitude and frequency of extreme precipitation are enhanced by expansions of urban area, irregularity, patch, dominance, and heat islands Duration of extreme precipitation is positive for the urban area and dominance but negative for irregularity, patch, and heat islands